THE EFFECTS OF WORK PASSION, WORK ENGAGEMENT AND JOB SATISFACTION ON TURN OVER INTENTION OF THE MILLENNIAL GENERATION - Sylvia Diana Purba; Andhie Novien Dwi Ananta (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
The purpose of this research was to observe the effect of work passion of the millennial workforces in Belant Persada Ltd on its turnover intention through work engagement and job satisfaction. The sample is all of the millenial workforces in Belant Persada Ltd, which are58 employees. The data were collected through questionnaires and analyzed using Macro PROCESS by Hayes and Preacher through Statistical Package for the Social Sciences (SPSS). The results showed that work passion significantly affects work engagement and job satisfaction. While the work passion and work engagement are not direct and significant impact on the turnover intention. Furthermore, job satisfaction brings a significantly negative effect on turnover intention. This research failed to prove the existence of variable work engagement as a mediating variable. On the other hand, job satisfaction successfully serves as a mediating variable. It presents that work passion can determine turnover intention through increasing the job satisfaction.